Transfer Pricing under Bilateral Bargaining - Peter Chalos; Susan Haka (The Accounting Review, 1990)
[Negotiation is frequently advocated as a transfer-pricing mechanism in decentralized organizations to foster greater divisional autonomy and to improve firm profit performance. Empirical evidence reveals that many firms rely upon negotiation in determining transfer prices. A concern, however, is that negotiation may not always be efficient in terms of maximizing firmwide profits, or equitable with regard to divisional performance evaluation. Given external market opportunities and private information with respect to divisional cost and revenue functions, one division could conceivably make itself better off at the expense of another or the firm as a whole. This study used a bilateral bargaining methodology to examine negotiated transfer-pricing outcomes between a buying and selling division. The negotiation was nonzero sum; that is, market externalities existed. Each division had private profit information. One hundred and thirty-four subjects participated in face-to-face negotiations. Experimental manipulation included a mixed-incentive (company and divisional) scheme versus a divisional-incentive scheme; single-period versus multiperiod negotiations; and varying levels of market price uncertainty in the negotiations. It was hypothesized that divisional-incentive schemes would increase profit differences between divisions but would be more effective in terms of maximizing overall company profits. Absent learning effects, a negotiation history was expected to increase company profits as bargaining strategies evolved over time. Finally, divisional profit differences were hypothesized to increase in the face of uncertain market alternatives available to either the buying or selling division. The results indicate that divisional incentives did not produce greater divisional profit differences than mixed incentives. However, as hypothesized, uncertain outside market alternatives significantly increased divisional profit differences. Company profits increased significantly under divisional incentives and through time. Finally, single-period profits were significantly lower than final multiperiod profits. The results have potentially important implications for research on negotiated transfer pricing under decentralization. First, divisional profit-based incentives appear to motivate negotiators to achieve higher company profits regardless of outside market alternatives. Bargaining strategies evolved over time, leading to an increase in company profits. Negotiated transfer prices, however, do not always attain the desired objective of maximizing companies' profits or providing equitable divisional performance evaluation. This was particularly true in cases of short negotiation histories and in cases of uncertain market environments. Results of this study suggest that one way to mitigate these dysfunctional consequences is through the company's incentive system. Mixed (company and divisional) incentives in uncertain environments appear to lead to more integrative agreements, benefiting both the company and the division. Because these results are based upon analysis of experiments, caution must be exercised in generalizing the conclusions beyond this setting.]